UPAYA PEMBENTUKAN BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) SEBAGAI BENTUK PERWUJUDAN PERLINDUNGAN KONSUMEN DI KOTA BENGKULU - Mikho Ardinata; Ahmad Dasan; Sinung Mufti Hangabei (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
Abstract: Consumer protection is an inseparable part of healthy business activity. In a healthy business activity there is a balanced relationship of legal protection between consumers and economic actors. The lack of balanced protection leads to a weak position for consumers, especially when the product is limited, so that economic operators can abuse their position by monopolizing production and marketing, which of course is very detrimental to consumers. The problems that arise are due to the lack of socialization in consumer protection, which in many cases leads to disputes between consumers and economic operators. Disputes that arise after consumers feel harmed by such business actors have resulted in the protection in Bengkulu City still being repressive. This is the background to the problem of the efforts to set up the Consumer Dispute Settlement Board (BPSK) as an administrative authority in the city of Bengkulu to protect consumer interests on the basis of Consumer Protection Act No. 8 of 1999.Keywords: Consumer protection, consumer dispute, BPSK